Sosialisasi Pemilih Pemula Pada SMA Negeri 1 Campalagian - Muhammad Syihabuddin taufiq; Achmad Fauzi Kusmin; Aco Nata Saputra; Hendrawan Hendrawan; Andi Nur Fiqhi Utami (Lembaga Penelitian Pengabdian kepada Masyarakat, 2024)
Political literacy education for students is the first step taken to foster correct political understanding. This is considered to have a positive impact on the political practice that students will carry out in the future. There are several stages carried out, namely: 1) Implementation of a political literacy workshop 2) Political education sharing session on December 25 2023. Implementation of activities is carried out using the offline/face-to-face method. This community service is carried out to provide political education to SMAN 1 Campalagian students. The results of community service carried out in the form of political literacy workshops and sharing sessions related to politics can provide political understanding and correct political practices for students so that they can become intelligent beginner voters.